On State-Dependent Delay Intuitionistic Fuzzy Partial Functional Differential Equations with Integral Boundary Conditions - Bouchra Ben Amma; Said Melliani; Lalla Saadia Chadli (Journal of Mathematics)
This paper addresses the issue of the existence and uniqueness of intuitionistic fuzzy solutions for some classes of partial functional differential equations with state-dependent delay in a new weighted complete metric space. Theorems on the existence and uniqueness of intuitionistic fuzzy solutions for these problems with integral boundary conditions are established under some sufficient assumptions. Some numerical examples of applications of the main result of this work are presented.